Anticorrosive paint with a modified zeolite as functional pigment for SAE 1010 steel protection - D'alessandro, Oriana (2020)
Purpose - To formulate and prepare a series of alkyd paints with new anticorrosive pigments, eco-friendly to the environment, based on a natural zeolitic rock modified by ion exchange to incorporate passivating cations.Design/methodology/approach - The electrochemical characterization of the painted steel was carried out by conductivity measurements, linear polarization tests, measurements of the corrosion potential and electrochemical noise measurements. Besides, accelerated tests in standard environmental chambers were also done. Findings - The results show that clinoptilolite- mordenite based pigments incorporated in the paint provide acceptable anticorrosive properties taking into account their low environmental impact and the use of a natural resource of low cost. The inhibitory efficiency of ZLa is higher than 80% and for ZPr is close to 70%. The electrochemical assays of the coated panels with the alkyd paints ZLa and ZPr shows similar behaviour.Research limitations/implications - In this work, good results were obtained with an alkyd resin but other resins could be tested. Paints could also be formulated with modified zeolites as a complement to others traditional anticorrosive pigments.Practical implications - These paints could be used for the protection of metal structures in low corrosive environments.Originality / value -There are not many published works using zeolites as anticorrosive pigments.